Automatic regulated temperature wax bath / Mohammad Fadhil Mohammad Liza, Muhammad Irfan Muhammad Nor & Muhammad Faiz Musa - Mohammad Liza, Mohammad Fadhil; Muhammad Nor, Muhammad Irfan; Musa, Muhammad Faiz (2014)
Paraffin wax bath is used to soothe chronic arthritis joint pain, to relax stiff muscles, and also to increase range of motion. The purpose to choose this project because this project will be upgrade the equipment that already have from taking wax temperature manually to the automatically taking wax temperature. This way can be increase the safety to user to use it from danger when doing checking wax temperature. So, this project use temperature sensor, which is LM 35 to sense the presence of the temperature of the wax. When the sensor detects the temperature above the desired temperature, the heater will off automatically heat the water and the paraffin wax. If the temperature below desired temperature, the heater will automatically on. This project uses many components, electronic components such as LCDs, PIC 16F876A, heater, relays, voltage regulator circuit. LCD function is to display the temperature reading so that users read the temperature of the wax quickly. Thus, this project is improvement version uses a sensor to measure the temperature of the wax is automatically and can save time.